Editors and Guidelines, SUSURGALUR Journal, issue of September 2015 - SUSURGALUR, Editor Journal (SUSURGALUR, 2015)
SUSURGALUR journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the history education and historical studies, and its various aspects. Analysis will be practical and rigorous in nature.Bandar Seri Begawan, Brunei Darussalam: September 30, 2015.Â Assoc. Prof. Dr. Haji Awang Asbol bin Haji MailVice Chief Editor of the SUSURGALUR Journal in Bandung, Indonesia; and Senior Lecturer at the Department of History FASS UBD (Faculty of Arts and Social Sciences, University of Brunei Darussalam) in Bandar Seri Begawan, Negara Brunei Darussalam.Â